Programa de juego libre en los sectores para el desarrollo de la creatividad en los estudiantes de nivel inicial de la Institución Educativa N° 62498 San Fernando Balsa Puerto, Alto Amazonas 2024 - Tamani Taminche, Karol Mariana (2025)
The general objective of this work was to evaluate the application of a free play program in sectors as a way of carrying out a teaching-learning process of creativity in early childhood education students at Educational Institution No. 62498 San Fernando, Balsa Puerto, in the 2024 school year. The pre-experimental approach was used, and the design was pretest/posttest with a single group, using quantification techniques. The sample consisted of 28 early childhood students chosen through non-probability convenience sampling. The intervention consisted of the implementation of a structured program of free play application in sectors with the purpose of enhancing the four objectives of creativity: fluency, flexibility, originality, and elaboration. For data analysis, the Student t-test for related samples was used; the assumption of normality was previously verified using the Shapiro Wilk test. The results showed significant improvements in overall creativity (tc = 5,320; p = 0,000), as well as in all its dimensions: fluency (tc = -4,309), flexibility (tc = -3,537), originality (tc = -3,758), and elaboration (tc = -4,893), all with significance levels of p < 0,05. A notable decrease was also observed in the low level of performance and an increase in the medium and high levels. It is concluded that the free play program implemented has a positive impact on the development of children's creativity and its continued application in early childhood education is encouraged.